Uniportal video-assisted thoracoscopic surgery right upper lobectomy with systematic lymphadenectomy in a semiprone position - Lin, Zongwu; Xu, Songtao; Wang, Qun (Journal of Thoracic Disease, 2014)
A 53-year-old male smoker was referred to our hospital with an enlarged lesion in the right upper lung. Computed tomography (CT) showed a 1.5 cm solid lesion with pleural indentation in the right upper lobe adjacent to the oblique fissure. The preoperative clinical diagnosis was stage I primary lung cancer. Uniportal video-assisted thoracoscopic surgery (VATS) right upper lobectomy in a semiprone position was performed in this case. Frozen section examination confirmed the diagnosis of lung adenocarcinoma, and systematic lymphadenectomy was then performed. A chest tube was placed at the posterior part of the incision through the dorsal thoracic cavity to the apex. The postoperative pathologic diagnosis was T2aN0M0 adenocarcinoma.